Perspectives of mutual encounters in South Asian history, 1760-1860 - Malik, Jamal (Social, economic, and political studies of the Middle East and Asia, 2000)
This volume explores the issues of cultural reciprocity between Europeans and South Asians. In doing so, prevailing assumptions about these complex relationships are examined